2013
DOI: 10.1073/pnas.1215283110
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic strategy as a tradeoff between energy yield and protein cost

Abstract: Contrary to the textbook portrayal of glycolysis as a single pathway conserved across all domains of life, not all sugar-consuming organisms use the canonical Embden-Meyerhoff-Parnass (EMP) glycolytic pathway. Prokaryotic glucose metabolism is particularly diverse, including several alternative glycolytic pathways, the most common of which is the Entner-Doudoroff (ED) pathway. The prevalence of the ED pathway is puzzling as it produces only one ATP per glucose-half as much as the EMP pathway. We argue that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
511
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(532 citation statements)
references
References 40 publications
21
511
0
Order By: Relevance
“…The fastest-growing cells-already taxed by limited glucose availability and therefore requiring efficient substratelevel ATP generation-must rely again on glycolysis, and can only maintain a high growth rate by having a correspondingly high enolase copy number. A recent analysis of enzyme kinetics in the glycolysis and ED pathways suggests that the ED pathway may be significantly more favorable in terms of enzymatic protein requirement (27). This could explain why the enolase copy number distribution appears to have evolved toward requiring the use of both pathways rather than exclusive use of glycolysis.…”
Section: Growth Rates and Flux Distributionsmentioning
confidence: 98%
“…The fastest-growing cells-already taxed by limited glucose availability and therefore requiring efficient substratelevel ATP generation-must rely again on glycolysis, and can only maintain a high growth rate by having a correspondingly high enolase copy number. A recent analysis of enzyme kinetics in the glycolysis and ED pathways suggests that the ED pathway may be significantly more favorable in terms of enzymatic protein requirement (27). This could explain why the enolase copy number distribution appears to have evolved toward requiring the use of both pathways rather than exclusive use of glycolysis.…”
Section: Growth Rates and Flux Distributionsmentioning
confidence: 98%
“…In wild-type cells, Crp1 appears to repress the ED pathway to ensure carbon is routed through the EMP pathway. Flamholz et al (2013) showed that the EMP pathway incurs a 3.5-fold higher protein cost compared with the ED pathway, but this is offset by the higher ATP yield of the EMP pathway versus the ED pathway. CRP mediates the hierarchical utilization of carbon sources in many bacteria, resulting in a diauxic pattern of growth (Saier, 1989).…”
Section: Crp1 Regulation Of Solute Transport and Carbon Metabolism Inmentioning
confidence: 99%
“…Like growth rate, growth efficiency integrates a microbe's physiology, ecology and evolutionary history. The efficiency of growth for any given microbe depends on multiple environmental and population-specific factors, including the free energy available from a resource (Linton and Stephenson, 1978), pathways for resource utilization (Flamholz et al, 2013), the availability of precursors for biomass synthesis (Stouthamer, 1973) and the fraction of available energy devoted to maintenance functions instead of growth (Hoehler and Jørgensen, 2013). We do not yet know the collection of specific genetic determinants that underlie growth efficiency, but as described below, it is obvious that efficiency is a life history trait and is under selection in most environments.…”
Section: Introductionmentioning
confidence: 99%